The influence of two decision-making styles on stress perception in military nursing students during clinical practice - Azzara, Sergio Héctor; Sol Grinhauz, Aldana (Decision Making and Analysis, 2024)
The primary objective of this study was to investigate how the tendency to make emotionally urgent decisions influences the perception of stressful situations in military nursing students during their clinical practice. A correlational cross-sectional design was employed, and data were collected from 79 cadets who were enrolled in a nursing program at the only Argentine military institution offering this degree. Two instruments were utilized: the Kezkak Inventory of Clinical Practice Stressors and the Inventory of Bases for Urgent Decision-Making in Extreme Circumstances. Simple linear regression analyses were conducted to assess the relationship between decision-making styles and specific stressful situations. The results indicated that the inclination to make emotionally urgent decisions was a significant predictor of overall stress perceptions and of specific situations in clinical practice, such as patient suffering, the inability to control the nurse-patient relationship, and the helplessness and uncertainty of not knowing how to proceed. This study highlighted the importance of developing emotional management skills in nursing students, particularly in military contexts, to assist them in making balanced and effective decisions in challenging clinical situations.